POLITIK INFORMAL DALAM INSTITUSIONALISASI DI PEMERINTAH KOTA YOGYAKARTA DI ERA HERRY ZUDIANTO - , erni zuhriyati, Nanang Indra Kurniawan, SIP, MA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to track the Government's efforts in the City Government of Yogyakarta in era Herry Zudianto for new values in a changing socio-political context. In an effort to institutionalize the value of democratization, transparantion, and accountabilitation, they pursue a multi-dimensional with a formal way, such as organizational regulations and legislation. However, Their successful also lies in the process of informal methods, namely through a method that emphasizes a personalized approach, communication and culture of Yogyakarta. Theoretically, the method is to affirm the theory of institutionalization B Guy Peter as saying that the process of institutionalization in the context of the change can be successfully performed if the sought has autonomization processes, adaptation, creative activity and lead to coherence between actors. Political institutionalizations in the informal communication are a lot of case with government officials, the Mayor and citizens, Coffee Morning, Kethoprak Birokrat, Sego Segawe, Wayang Pesisiran, Walikota Menyapa, and so on. Institutionalization is a significant process in an effort to alter the performance of governance reform in Indonesia, because in the process there is an attempt to internalize the new values towards the performance of government more democratic, transparent and accountable. Governance reform is not enough just to make the change of organization or a formal assessment as required in the paradigm of good governance, but the most significant reform is the effort to change the paradigm of performance and internalize the value and changes the government's performance. This study is a qualitative research to interpret data,obtained from interviews with informants in the government environment of Yogyakarta and secondary data analysis and documentation writing.